2022
DOI: 10.1055/a-1635-6112
|View full text |Cite
|
Sign up to set email alerts
|

Snare tip soft coagulation (STSC) after endoscopic mucosal resection (EMR) of large (> 20 mm) non pedunculated colorectal polyps: a systematic review and meta-analysis

Abstract: Background and study aims Endoscopic mucosal resection (EMR) of laterally spreading tumors (LSTs) > 20 mm in size can be challenging. Piecemeal EMR of these lesions results in high rates of adenoma recurrence at first surveillance colonoscopy (SC1). Snare tip soft coagulation (STSC) of post resection margins is a safe and effective technique to prevent adenoma recurrence. We conducted a systematic review and meta-analysis to evaluate the effectiveness and safety of this technique. Patients and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Intraprocedural bleeding occurred in 13% of patients included in the single study that quantified this parameter [ 10 ]. These values are identical to those reported for STSC-assisted EMR, where intraprocedural and delayed bleeding are estimated to occur in 10% and 6.5%, respectively [ 13 ]. However, no studies compared directly hAPC with the currently preconized margins’ ablation methods (standard APC and STSC).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Intraprocedural bleeding occurred in 13% of patients included in the single study that quantified this parameter [ 10 ]. These values are identical to those reported for STSC-assisted EMR, where intraprocedural and delayed bleeding are estimated to occur in 10% and 6.5%, respectively [ 13 ]. However, no studies compared directly hAPC with the currently preconized margins’ ablation methods (standard APC and STSC).…”
Section: Discussionsupporting
confidence: 86%
“…Five studies evaluated the recurrence of intestinal metaplasia [ 4 , 9 , 10 , 13 , 15 ]. Knabe et al [ 9 ] found a histologic recurrence rate of 29.2% ( Table 1 ; Figure 3 ) after 24 months of follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrespective of the EMR technique used, the endoscopist decided to attempt the closure of the mucosal defect with clips and the thermal ablation of its margins with snare tip coagulation, as recommended in the literature [ 17 ]. It should be noted that margin thermal treatment of the margins had not been employed in the initial years of our retrospective analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the differences in techniques compared to hot EMR, it is suggested that cold snare resection be performed by using a dedicated cold snare while aiming for smaller pieces with attention to overlapping and obtaining wide healthy margins. Thermal ablation of the defect margin after EMR of large nonpedunculated colorectal polyps has been shown to significantly reduce residual or recurrent adenoma at first surveillance colonoscopy and is therefore recommended as adjunct therapy [ 35 , 36 , 37 ]. Another variant of cold EMR can also be performed underwater, known as underwater EMR (uEMR), which has the benefit of not requiring submucosal injection.…”
Section: Endoscopic Approaches To Therapymentioning
confidence: 99%